The erosive potential of flavoured sparkling water drinks - CATRIONA J. BROWN, GAY SMITH, LINDA SHAW, JASON PARRY & ANTHONY J. SMITH (IAPD and Blackwell, 2007)
The potential role of acidic drinks in the aetiology of dental erosion is well recognized. Whilst the wide-scale consumption of bottled waters is unlikely to contribute significantly to erosion, the role of flavoured sparkling water drinks is unclear.